BLOOD DONATION IN MAHARASHTRA: PREVALENCE OF TRANSFUSION TRANSMITTED INFECTIONS IN BLOOD DONORS - A.SONAWANE PATIL,; A SHANKARKUMAR PAWAR, (International Journal of Pharma and Bio Sciences, 2015)
Transfusion transmitted infections (TTI) create a significant burden on health care system. Donor selection is of paramount importance because infected individuals serve as an asymptomatic reservoir and a potential source of transmission. The present study was carried out to find out the prevalence of Transfusion transmitted Infections (TTI) in blood donors of Maharashtra region. A retrospective study was carried out in healthy blood donors of NACO assisted blood banks in Maharashtra over a period of seven years from January 2008 to December 2014, to determine the prevalence of HIV, HBV, HCV, syphilis and malaria in blood donors. The prevalence of TTIs among the total collected blood was 20271(0.40) for HIV1 and 2, 75266(1.48%) for HBsAg, 19022 (0.37%) for HCV, 5651 (0.11%) for Syphilis and 838 (0.02%) for malaria. The HBsAg percentage of TTI positivity detected in blood donors of Maharashtra is high. That may be due to the stringent follow up of testing or may be due to compromised testing quality.